(untitled) (Bangladesh Journal of Medical Science, 2011)
Experiences with management of 140 (82 males and 58 females) patients of brucellosis is presented. The diagnostic criteria was based on clinical presentation (fever, joint pains) and high titre positive brucella agglutination test. Forty-four (31.4%) patients responded in 2-9 days as evidenced by high temperature coming to normal on receipt of adequate therapy by tetracycline alone or in combination with streptomycin or other drugs. Inappropriate antibiotic in inappropriate doses was given to 23 (16.4%) patients resulting in a slow response. More than half 73 (52%) were not treated as they did not attend for follow up for result of investigation or misdiagnosis. The complications were bone and joint involvement and endocarditis. To give adequate therapy and avoid complications any patient with pyrexia in Saudi Arabia should be investigated for brucellosis. DOI: http://dx.doi.org/10.3329/bjms.v3i1.8222 BJMS 1996; 3(1): 16-20